Modeling and Simulation of Series-parallel UMT PHEV Powertrain - Nur Haezah, M; H. Atiq, W; S. Norbakyah, J; R. Salisa, A (International Journal of Engineering and Technology, 2018)
This paper presents a modeling and simulation of Universiti Malaysia Terengganu (UMT) plug-in hybrid electric vehicle (PHEV) powertrain. There are four main components of UMT PHEV are modeled, which are internal combustion engine, electric machine, battery and ultracapacitor. Firstly, the vehicle components are sized through a power flow analysis to meet the expected power and the energy requirements. Then, a mathematical model of each component is obtained and simulated in MATLAB/SIMULINK environment. As the results, all the simulation results seem that the pattern of graph and the range of value are in reasonable.Â  It can be concluded that all main components models are correct.Â Â